2017
DOI: 10.32007/med.1936/jfacmedbagdad.v59i3.11
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Preventive Foot Care Practices among Patients with Diabetes Mellitus Type II

Abstract: Background: Diabetic foot problems are one of the most important complications of diabetes mellitus which causing a worldwide high cost morbidity which could be due to poor self-practices. Objectives: To assess the preventive food care practices among diabetic patients and to find out any significant association of these practices with selected socio-demographical and diabetic related characteristics. Patients and Methods: A descriptive cross-sectional study was conducted in Baquba city from the period of 20 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 9 publications
7
3
1
Order By: Relevance
“…Regarding foot care awareness current study founded that 20% with poor care, 44% with satisfactory and 36% with good awareness, in other study in Iraq 37.5% with poor awareness and 62.6% with good awareness (14) , from India there was two studies one of them founded that 40% with good practiceand 60% with poor practice (17) , other study show 15% with adequate knowledge, 53% with moderate knowledge and 32% is inadequate knowledge (18) , Other two studies from Saudi Arabia the patients with good foot care 77% while 23% for the bad foot care (12) , 53.3% with high level of knowledge and 46.7% with low knowledge (19) but a study from Al Bahrain revealed that good 20.4%, satisfactory 37%, and poor knowledge 42.6% (15) . The analysis of foot care assessment score revealed that 73.3% of the patients inspect their feet and look for any new red spots/cuts/swelling or blisters, in other study from Iraq 59.2% daily self-foot inspection and 17.5% sometimes (14) , 76.9% according to study from Saudi Arabia (13) , in another study from India 62.9% (17) . About 83.3% of patients in this study practicing daily feet washing, a study in Saudi Arabia with 96.3% (13) and 96.6% from Bahrain (15) the Islamic rituals ablution before offering prayers was the participants practicing washing of the feet daily, but the space between toes should be dried.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…Regarding foot care awareness current study founded that 20% with poor care, 44% with satisfactory and 36% with good awareness, in other study in Iraq 37.5% with poor awareness and 62.6% with good awareness (14) , from India there was two studies one of them founded that 40% with good practiceand 60% with poor practice (17) , other study show 15% with adequate knowledge, 53% with moderate knowledge and 32% is inadequate knowledge (18) , Other two studies from Saudi Arabia the patients with good foot care 77% while 23% for the bad foot care (12) , 53.3% with high level of knowledge and 46.7% with low knowledge (19) but a study from Al Bahrain revealed that good 20.4%, satisfactory 37%, and poor knowledge 42.6% (15) . The analysis of foot care assessment score revealed that 73.3% of the patients inspect their feet and look for any new red spots/cuts/swelling or blisters, in other study from Iraq 59.2% daily self-foot inspection and 17.5% sometimes (14) , 76.9% according to study from Saudi Arabia (13) , in another study from India 62.9% (17) . About 83.3% of patients in this study practicing daily feet washing, a study in Saudi Arabia with 96.3% (13) and 96.6% from Bahrain (15) the Islamic rituals ablution before offering prayers was the participants practicing washing of the feet daily, but the space between toes should be dried.…”
Section: Discussionsupporting
confidence: 50%
“…Only 40% of patients in this study applying lotion/moisturizer on the top/button of the feet but not between toes, close to other study 48.7% put moisturizing lotion on feet daily (15) but 28.6% regarding study in India (16) .Moisturizing skin with a suitable cream or lotion can restore skin elasticity and softness by improving cell hydration, This unsatisfactory finding might be explained by the fact that the eastern human regarding moisturizing a skin as shameful act, many of people thought that lotion is cosmetic material only. About 64% of the patients trimming toenail straightly and full edges in this study, in other study 61.81% (17) , other study in Iraq 45.8% always tacking care when clipping their toenail but 2.5% sometimes tacking care when clipping their toenail, and 48.3% always not using sharp scissor to nail cutting but 9.2% sometimes using sharp scissor to nail cutting (14) . In this study 82% of the patients knows that they should not walking barefoot and 79.3% wear shoes/slippers both indoors and outdoors, According to study in Bahrain 42.6% walking bare foot (15) , and 39.3% according to study in India (10) , this difference in results because walking bare foot is common in the previously mentioned countries.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations